2018
DOI: 10.1017/s1049096518000902
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Games for Teaching Political Science Methodology

Abstract: Students often find lectures on political science methodology difficult to grasp. Based on our success of simulations and games in teaching various political science theories, we created several mini-games to help students gain exposure in engaging ways with aspects of quantitative and qualitative methodology. We use techniques in which students learn through "gimmicks" (Schacht and Stewart 1990;1992), for which they are the data points that they are studying. We believe that drawing conclusions based on what … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Mini games have attracted increasing attention as educational tools that have the potential to teach difficult concepts to students (Asal et al, 2018 ). What is a mini game?…”
Section: Background and Theoretical Frameworkmentioning
confidence: 99%
“…Mini games have attracted increasing attention as educational tools that have the potential to teach difficult concepts to students (Asal et al, 2018 ). What is a mini game?…”
Section: Background and Theoretical Frameworkmentioning
confidence: 99%
“…Furthermore, Mendenhall and Tutunji (2018, 440) suggested that alternative teaching methods should have "low preparation time, minimal resource requirements, and ease of integration with existing curricula." Similarly, Asal et al (2018) pointed out that using simple gimmicks can be effective in teaching political science methodology. This mini-simulation follows those valuable suggestions in that there is little to no preparation time, no extra resources are required, and it is a low-intensity activity that students positively comment on in evaluations months afterwards.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, the state and its aristocratic elites may find themselves in a pre-revolutionary situation vulnerable to sudden shocks (e.g., famines and defeat in war) that further alter dissident decision-making calculus. 2 It is interesting that although there are many simulations and games related to IR (Starkey and Blake 2001) and interstate conflict (e.g., Haynes 2015;Kanner 2007;McCarthy 2014), there are relatively few related to comparative politics (e.g., Archer and Miller 2011;Asal et al 2017;Asal et al 2018;Shellman 2001). There are even fewer available games that focus on revolutions and why they start, although some explore civil war termination (Shaw 2006).…”
Section: Teaching About Exploitation and Revolutionmentioning
confidence: 99%